2020
DOI: 10.1080/00015385.2020.1820683
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and cost of FH cascade screening in Belgium (BEL-CASCADE) including a novel rapid rule-out strategy

Abstract: Background: Familial hypercholesterolaemia (FH) is underdiagnosed in most countries. We report our first experience from a national pilot project of cascade screening in relatives of FH patients. Methodology: Participating specialists recruited consecutive index patients (IP) with Dutch Lipid Clinic Network (DLCN) score 6. After informed consent, the relatives were visited by the nurses to collect relevant clinical data and perform blood sampling for lipid profile measurement. FH diagnosis in the relatives was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The direct method of cascade testing contact in relatives was used in 11 studies [22,24,27,29,31,35,36,38,40,42,44], and a further eight studies used an indirect method [21,25,26,[32][33][34]37,43]. The remaining five studies used a combination of direct and indirect methods [23,28,30,39,41], where the decision regarding which method was used was decided by the index case.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The direct method of cascade testing contact in relatives was used in 11 studies [22,24,27,29,31,35,36,38,40,42,44], and a further eight studies used an indirect method [21,25,26,[32][33][34]37,43]. The remaining five studies used a combination of direct and indirect methods [23,28,30,39,41], where the decision regarding which method was used was decided by the index case.…”
Section: Resultsmentioning
confidence: 99%
“…Forward cascade testing was used in the majority of included studies (23 studies), with the remaining study using reverse cascade testing [42]. Fourteen of the included studies reported the extent of cascade; the majority cascaded to second degree relatives (eight studies [21,22,26,31,35,38,40,43]), with only five studies cascading to first degree [24,27,32,39,44] and one study cascading to third degree [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations